Product service value analysis: two complementary points of view - Alix, T.; Ducq, Y.; Vallespir, B. (Cranfield University Press, 2009)
Product Service System is an innovation strategy, used by manufacturers to increase their competitiveness, while satisfying specific customer needs. Here the focus is on the additional services associated to products and precisely on their value to determine their position in firms’ portfolio and by extension their legitimacy to reach the implied objective of profitability. The study rests on the use of the value analysis methodology and compares the value of the offer for the manufacturer taking account of its expected benefits and the value of the same offer for customers defined by the way of expected quality criteria.
Organised by: Cranfield University
Keywords: Product-service; value analysis; product service oriented PSS; customer loyalty; innovation strategy